Anomalous pulmonary venous drainage shown by duplex sonography, computed tomography, and plain radiography. Issue 1 (January 1989) - Huebsch, P; Neuhold, A; Mayr, H; Glogar, D
Abstract : In a patient with the scimitar syndrome duplex Doppler sonography was used to show the point of entry of the abnormal pulmonary vein into the inferior vena cava to determine blood flow. Chest radiography and computed tomography also showed the vein descending to the diaphragm.